Interview with Estíbaliz Pérez Pérez. Digital Technologies for the Improvement of the Teaching and Learning Process - Pérez Pérez, Estíbaliz (2017)
The objective of this interview is to analyze the importance of digital technologies as a tool for improving the teaching and learning process. For Estíbaliz Pérez, digital technologies can be motivating elements for students, since the use of technology is part of the student’s daily life. It also states that technologies alone do not have the capacity to improve teaching and learning processes, since a process of teacher mediation that meets basic principles of educational quality is required, since its use must be relevant, relevant and equitable.